IMPLEMENTASI PENDIDIKAN NILAI DALAM PENDIDIKAN AGAMA ISLAM - Imelda, ade (Universitas Islam Negeri Raden Intan Lampung, 2015)
Education is at the core values of Islamic religious education, for the purpose ofeducation is to educate the value of human behavior in the teachings of Islam, better known byeducating noble character is based on the Quran and Hadith. Through education values, theobjectives, materials, methods, evaluation, and educators in Islamic religious education shouldsupport the achievement of educational goals that value. Implementation of values educationsince Islamic religious education can help learners become humans who understand the values oftheir religion and apply these values in their daily lives, so that any negative effects of thechanging times can be anticipated with better learners.